Successful Treatment with Pemetrexed, Carboplatin, and Bevacizumab for Platinum-Resistant Adenocarcinoma of the Lung - Sae Wada; Nobukazu Fujimoto; Kenichi Gemba; Michiko Asano; Yasuko Fuchimoto; Katsuichiro Ono; Shinji Ozaki; Takumi Kishimoto (Case Reports in Oncological Medicine)
We present two cases of relapsed adenocarcinoma of the lung: a 50-year-old male and a 67-year-old male. Both patients had previously been treated with platinum-containing systemic chemotherapy. In both cases, significant clinical efficacy was demonstrated with combination chemotherapy consisting of pemetrexed, carboplatin, and bevacizumab as salvage treatment. Adverse events were mild. This regimen might be a viable therapeutic option even after heavy treatment such as platinum-containing chemotherapy, especially for patients with preserved organ function and good performance status.